Análise dos parâmetros biomoleculares em corredores de ultramaratona - Ribas, Marcelo Romanovitch (2023)
Despite the known effects of the ACTN3 R577X, ACE I/D, and CK MM A/G NcoI polymorphisms on muscle proteins, their impact on electrochemical variables, acidbase disturbances, body composition, and performance in 105 km mountain ultramarathon runners is not yet fully understood. This study aimed to investigate the influence of these polymorphisms on electrochemical variables, acid-base disturbances, anthropometric changes, and running time in 22 male Brazilian elite mountain ultramarathon runners (35.9 ± 6.5 years). Body composition was determined using bioimpedance with the Maltron BF-906 device, while blood analyses were performed on the GEM Premier 3000 Gasometry equipment. Genotyping for R577X (RR, RX, and XX), ACE I/D (DD, ID, and II), and CK MM A/G NcoI polymorphisms was performed via Polymerase Chain Reaction–Restriction Fragment Length Polymorphism (PCR-RFLP) using DNA extracted from saliva. Results indicated a lower total body mass loss, BMI, and fat-free mass associated with shorter running times (Rs 0.52; p=0.01; 0.53; p=0.01; 0.47; p=0.02, respectively). Pre- and post-race weight differences were observed in athletes with the AA genotype vs. AG genotype (p = 0.02; p = 0.02). The RR genotype exhibited a correlation between BMI and running time (R = 0.97; p = 0.004). Genotype II showed a correlation with % body fat and fat mass in relation to running time (R = 0.91; p = 0.003; R = 0.99; p < 0.0001). Regarding Hct, the XX genotype of ACTN3 R577X displayed higher post-race values compared to the RX genotype (p=0.03). In terms of pH, the II genotype of ACE I/D showed higher post-race values than the ID genotype (p=0.02). PCO2 values were lower for the II genotype compared to the ID genotype post-race (p=0.01). In conclusion, the ACTN3 R577X, ACE I/D, and CK MM A/G NcoI polymorphisms have a significant impact on key performance-related variables in 105 km mountain ultramarathon runners.